The Indonesian Brahmāṇḍapurāṇa: translated from the original classical Kawi text - Phalgunadi, I. Gusti Putu (Sundeep Prakashan, 2000)
English translation of Indonesian Brahmāṇḍapurāṇa based on Sanskrit Brahmāṇḍapurāṇa.